Assessment of Interleukin‐18 gene polymorphism and serum levels in oral lichen planus in an Indian population. (7th February 2019) - Negi, Deepika; Urs, Aadithya B.; Kumar, Priya; Mahajan, Bhawna; Singh, Hanspal; Polipalli, Sunil K.; Kapoor, Seema
Abstract : Background: Oral lichen planus (OLP) is a chronic, inflammatory disease with uncertain etiology. The aim of this study was to assess Interleukin‐18 (IL‐18) gene polymorphism and serum levels in OLP cases of Indian origin and to compare them with a control population of similar background. Methods: The assessment of single‐nucleotide polymorphisms (SNPs) of IL‐18 gene at promoter regions −137(G/C) and −607(C/A) was done in 70 OLP cases and 70 healthy controls using sequence‐specific primer‐polymerase chain reaction (SSP‐PCR). In a subset of this cohort, comprising of 41 OLP cases and 41 controls, serum IL‐18 levels were assessed using enzyme‐linked immunosorbent assay (ELISA). Results: Mean serum levels of IL‐18 among OLP cases were significantly higher when compared to controls. Genotypic and allelic frequencies of IL‐18 at position −137(G/C) showed that GG genotype and allele G was significantly higher in OLP cases, whereas, GC genotype and C allele was high in the control group. Polymorphism of IL‐18 at position −607(C/A) showed no significant differences. Conclusions: Gene polymorphism at −137GG genotype and allele G seems to be associated with genetic susceptibility to OLP whereas −137GC and allele C may have a protective role against its development. However, our study lacks clear statistical correlation, the differences observed could be caused by sampling problems and the results could not be fully representative of Indian patients with OLP. Further studies are warranted to explore the role of IL‐18 genetic polymorphisms in OLP development.